2012
DOI: 10.1126/science.1212382
|View full text |Cite
|
Sign up to set email alerts
|

Female Leadership Raises Aspirations and Educational Attainment for Girls: A Policy Experiment in India

Abstract: Exploiting a randomized natural experiment in India, we show that female leadership influences adolescent girls’ career aspirations and educational attainment. A 1993 law reserved leadership positions for women in randomly selected village councils. Using 8,453 surveys of adolescents aged 11–15 and their parents in 495 villages, we find that, compared to villages that were never reserved, the gender gap in aspirations closed by 25% in parents and 32% in adolescents in villages assigned to a female leader for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
593
5
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 912 publications
(632 citation statements)
references
References 29 publications
26
593
5
8
Order By: Relevance
“…3 Following Beaman et al (2012) and , the aspirations level was calculated using an aggregate index based on respondents' answers to questions about their aspirations in the four dimensions. The aggregate aspirations index was then used to classify individuals into low-aspirations and high-aspirations status relative to the district average.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…3 Following Beaman et al (2012) and , the aspirations level was calculated using an aggregate index based on respondents' answers to questions about their aspirations in the four dimensions. The aggregate aspirations index was then used to classify individuals into low-aspirations and high-aspirations status relative to the district average.…”
Section: Datamentioning
confidence: 99%
“…In this regard, in rural Ethiopia, Bernard et al (2011) and Bernard and Taffesse (2012) found evidence that low aspirations are correlated with low demand for long-term loans and low use of such loans for long-term investments. Elsewhere, other studies have found strong correlations between aspirations and: expenditures on agricultural inputs, yields, and savings (Kosec et al 2012), savings choices and health-seeking behavior (Ghosal et al 2013), private school enrolment (Galab et al 2013), educational outcomes (Serneels and Dercon 2014), dropout behaviour (Goux et al 2014), career aspirations and educational attainment of adolescent girls (Beaman et al 2012), and risky choice behaviour (Payne et al 1981). Further, based on a randomized control, showed that aspirations can be altered, implying that a potential role for policy exists.…”
Section: Introductionmentioning
confidence: 99%
“…In housing, imperfections due to thin markets can be large and further exacerbated by choice restrictions due to quotas because of the two types of choice heterogeneity (segregation preferences and thin markets) highlighted in my model. 50 For example, Beaman et al (2012) quantify the benefit of introducing gender quotas in politics and Edin, Fredriksson, and Åslund (2004) study the benefits of a residential desegregation policy on immigrants. 51 In a decentralized equilibrium, the first best allocation of ethnic groups may not be achieved because of externalities (An individual chooses the neighborhood that maximizes his own utility, without internalizing the effect of his choice on the ethnic proportions in the neighborhood).…”
Section: Resultsmentioning
confidence: 99%
“…A role-model effect implies that female leaders are effective in motivating women, changing their attitudes, perceptions, and demand for social services. (Beaman et al, 2012). It is quite possible that improved access, as well as increased demand for health services may have been influenced by this policy change.…”
mentioning
confidence: 99%